1989
DOI: 10.1210/jcem-69-5-1040
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Serum Dehydroepiandrosterone Sulfate Levels by Insulin: An Evaluation of Possible Mechanisms *

Abstract: We previously demonstrated a progressive decline in serum dehydroepiandrosterone sulfate (DHEA-S) levels in women during a hyperinsulinemic-euglycemic clamp. To determine whether this fall in serum DHEA-S levels might have been due to insulin-stimulated 1) hydrolysis of DHEA-S to dehydroepiandrosterone (DHEA), 2) conversion of DHEA-S/DHEA to androstenedione, and/or 3) urinary excretion of these steroids, 10 additional men were studied by the hyperinsulinemic-euglycemic clamp technique. Each man received a 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
64
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 24 publications
11
64
1
1
Order By: Relevance
“…As discussed above, DHEAS levels, in relation to enhanced insulin secretion, may even be reduced as a result of increased metabolic turnover of this hormone (22)(23)(24)(25)(26). In fact, there are yet other factors in addition to IGF-I or leptin, which increase with body size or obesity and stimulate adrenal steroids, but their investigation could not be carried out in this study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As discussed above, DHEAS levels, in relation to enhanced insulin secretion, may even be reduced as a result of increased metabolic turnover of this hormone (22)(23)(24)(25)(26). In fact, there are yet other factors in addition to IGF-I or leptin, which increase with body size or obesity and stimulate adrenal steroids, but their investigation could not be carried out in this study.…”
Section: Discussionmentioning
confidence: 87%
“…In obese women, DHEAS levels are slightly increased and independent of insulin secretion, but positively correlated with IGF-I (21). In contrast, in adult men with obesity (22) and hyperinsulinaemia (23,24) DHEA(S) is decreased. Levels of dehydroepiandrosterone or DHEAS are similarly reduced in women with severe obesity or type 2 diabetes (25,26).…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, Nestler and colleagues (1987) studied the effects of insulin on serum DHEAS levels in women during a hyperinsulinaemiceuglycaemic clamp and found that insulin had a suppressive effect. When these findings were further investigated by repeating the study in men, both DHEAS and DHEA levels fell progressively and proportionally (Nestler et al 1989). Interestingly, androstenedione levels also fell in Figure 1 Sulphatase activity measured by production of DHEA from DHEAS substrate (31 nM) in granulosa cells cultured in the presence or absence (control) of (a) LH at 0·25-5 ng/ml, (b) insulin at 0·25-10 ng/ml or (c) the specific sulphatase inhibitor EMATE at 1-5000 nM.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 In women, however, a prospective study failed to ®nd any relationship between DHEAS concentrations and ischaemic heart disease (IHD). 8 Experimentally induced hyperinsulinaemia lowers DHEAS concentrations 5 and weight loss decreases plasma insulin concentrations. 9 A reduction in weight may result in a decrease in insulin and therefore an increase in DHEAS, so contributing the ultimate reduction in IHD risk.…”
Section: Introductionmentioning
confidence: 99%